Surface immobilization of hexa-histidine-tagged adeno-associated viral vectors for localized gene delivery - Jang, Jae-Hyung (2010)
Adeno-associated viral vectors, which are undergoing broad exploration in clinical trials, have significant promise for therapeutic gene delivery due to their safety and delivery efficiency. Gene delivery technologies capable of mediating localized gene expression may further enhance AAV’s potential in a variety of therapeutic applications by reducing spread outside of a target region, which may thereby reduce off-target side effects. We have genetically engineered an AAV variant capable of binding to surfaces with high affinity via a hexahistidine-metal binding interaction. This immobilized AAV vector system mediates high efficiency delivery to cells that contact the surface and thus may have promise for localized gene delivery, which may aid numerous applications of AAV delivery to gene therapy.